Medina Sierra, Luis Fernando (2019). Socialismo, historia y utopía. Apuntes para su tercer siglo. Akal. 176 páginas - Sánchez Berrocal, Alejandro (Las Torres de Lucca. International Journal of Political Philosophy, 2021)
How is it possible that "socialism" is a living idea today? How does it push us to a review of its complex heritage and an inquiry into its perspectives? What is the old and the new that socialism implies for the 21st century? After decades of neoliberal counterrevolution, the twilight of "really existing communism", the stories about the "end of history" and the (supposed) entry into a "post-political" and "post-ideological" era, it may come as a surprise that the questions with which We open this review continue to constitute theoretical problems of the first order. And yet the son.